Hydroxymethyl-Branched Piperidines from Hydroxymethyl-Branched Lactones: Synthesis and Biological Evaluation of 1,5-Dideoxy-2-C-hydroxymethyl-1,5-imino-D-mannitol, 1,5-Dideoxy-2-C-hydroxymethyl-1,5-imino-L-gulitol and 1,5-Dideoxy-2-C-hydroxymethyl-1,5-imino-D-talitol - Soengas, R; Simone, M; Hunter, S; Nash, R; Evinson, E; Fleet, G (2012)
Three homochiral polyhydroxylated piperidines containing a quaternary carbon branch at C-2 of the heterocyclic ring, which can be considered as branched analogues of deoxymannorijimycin (DMJ), and their corresponding lactams were synthesised from readily available and versatile carbohydrate lactones containing a 2-C-hydroxymethyl branch. The key step in the synthesis of these iminosugars, 1,5-dideoxy-2-C-hydroxymethyl-1,5-imino-D-mannitol, 1,5-dideoxy-2-C-hydroxymethyl-1,5-imino-L-gulitol and 1,5-dideoxy-2-C- hydroxymethyl-1,5-imino-D-talitol, was an efficient modified Kiliani reaction performed on the readily available ketose starting materials L-sorbose and D-fructose. The introduction of the carbon branch at C-2 resulted in loss of glycosidase inhibitory activity, which could be advantageous for therapeutic use of such compounds as chaperones. Here we report the preparation of three branched iminosugars, which can be considered as analogues of deoxymannorijimicin (DMJ) containing a quaternary carbon branch at C-2, and their corresponding lactams. The starting materials are branched sugar lactone intermediates, which in turn were afforded by a modified Kiliani procedure from L-sorbose and D-fructose. © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.